THE INFLUENCE OF MOTIVATION AND JOB PLACEMENT ON VOCATIONAL SCHOOL TEACHER PERFORMANCE IN SUKABUMI CITY (Proceeding of SINERGY, 2026)
This study aims to analyze the influence of motivation and job placement on the performance of vocational high school teachers in Sukabumi City. The background of the study is based on the teacher performance assessment of 96.99% in 2024, which is still below the target of 100% and the importance of improving the quality of teacher performance as a determining factor for the success of the educational process in vocational high schools, especially in facing the challenges of the globalization era and job market needs. The study used a quantitative approach with a survey method of 100 respondents selected through the Slovin sampling technique from a population of 642 vocational high school teachers. The research instrument was a Likert-scale questionnaire that had undergone validity and reliability tests. Data analysis was carried out through classical assumption tests, multiple linear regression, t-tests, F-tests, and coefficients of determination (R²). The results of the study indicate that motivation and job placement each have a positive and significant effect on teacher performance, both partially and simultaneously. The job placement variable has a more dominant influence than motivation, with a larger regression coefficient and a significance level of 0.000. Simultaneously, the two variables explained 67.4% of the variation in teacher performance, while the remaining 32.6% was influenced by factors outside the research model. These findings confirm that increasing motivation and appropriate job placement are important strategies for improving the performance of vocational high school teachers in Sukabumi City. This research is expected to serve as a reference for schools and policymakers in designing more effective and sustainable human resource management policies.